Mobile Phone Coverage and Producer Markets : Evidence from West Africa - Aker, Jenny C.; Fafchamps, Marcel (World Bank Group, Washington, DC, 2014)
Mobile phone coverage has expanded considerably throughout the developing world, particularly within sub-Saharan Africa. Existing evidence suggests that increased access to information technology has improved agricultural market efficiency for consumer markets and certain commodities, but there is less evidence of its impact on producer markets. Building on the work of Aker (2010), this paper estimates the impact of mobile phone coverage on producer price dispersion for three commodities in Niger. The results suggest that mobile phone coverage reduces spatial producer price dispersion by 6 percent for cowpea, a semi-perishable commodity. These effects are strongest for remote markets and during certain periods of the year. The introduction of mobile phone coverage has no effect on producer price dispersion for millet and sorghum, two staple grains that are less perishable and are commonly stored by farmers. There are no impacts of mobile phone coverage on traders' gross margins or producer price levels, but mobile phone coverage is associated with a reduction in the intra-annual price variation for cowpea. These results are potentially explained by the fact that farmers engage in greater storage for storable commodities such as millet and sorghum.